Developing and prioritising strategies to improve the implementation of maternal healthcare guidelines in South Africa: The nominal group technique - Thifhelimbilu I. Ramavhoya; Maria S. Maputle; Tinyiko R. Lebese (AOSIS, 2022)
Background: In South Africa, maternal healthcare guidelines are distributed to primary health care (PHC) facility for midwives to refer and implement during maternal healthcare services. Different training was offered for the use of maternal care guidelines. However, poor adherence and poor implementation of guidelines were discovered. Aim: This study aimed to develop and prioritise strategies to improve the implementation of maternal healthcare guidelines at PHC facilities of Limpopo province, South Africa. Method: Strengths, weaknesses, opportunities and threats analysis and its matrix together with the nominal group technique were used to develop the current strategy. Midwives, maternal, assistant and operational managers from PHC facilities of the two selected district of the Limpopo province were selected. Criterion-based purposive sampling was used to select participants. Data collection and analysis involved the four steps used in the nominal group technique. Results: Strategies related to strengths and weaknesses such as human resources, maternal health services and knowledge deficit were identified. Opportunities and threats such as availability of guidelines, community involvement and quality assurance as factors that influenced the provision of maternal healthcare services were identified. Conclusion: Researchers formulated actions that could build on identified strengths, overcome weaknesses such as human resources, explore opportunities and mitigate the threats such as quality assurance. Implementation of the developed strategies might lead to the reduction of the maternal mortality rate.